Cloud-Controlled Parcel Storage Box with User Image Capturing - Yeow Guo Geng; Soom Chin Fhong (Evolution in Electrical and Electronic Engineering, 2022)
Nowadays, the pandemic COVID-19 has caused people mostly work from home and spend less time staying at the office to avoid close contact with other people. This causes difficulty in parcel delivery when there is no worker at the office. Thus, a cloud-controlled parcel storage box with user image capture is designed to overcome the problem. The box is implemented with the technology of a door lock system and motion alert system by using the microcontroller NodeMCU ESP8266, ESP32-CAM and the Blynk IoT platform. The box is allowed to be controlled by using the Blynk and the vision image will be taken when motion is detected. The time response for the solenoid door lock and magnetic door sensor is less than 1 second. The percentage to obtain a clear vision image is 70% and the average time taken for ESP32-CAM to send the image to telegram is 5.64 seconds. This project contributes to the parcel delivery system to easily pick up and drop off the parcel. In the future, it is recommended to implement a face recognition or face detection system to allow the door to open automatically.